Combinational elastography for assessment of liver fibrosis in patients with liver injury. Issue 6 (June 2022) - Yazaki, Tomotaka; Tobita, Hiroshi; Sato, Shuichi; Miyake, Tatsuya; Kataoka, Masatoshi; Ishihara, Shunji
Objective: We investigated the utility of combinational elastography with point shear wave elastography (pSWE) and real-time tissue elastography (RTE) for evaluating liver fibrosis in patients with liver injury. Methods: In this prospective single-institution study, patients scheduled for a liver biopsy to determine the presence of liver disease were enrolled. Liver fibrosis in each patient was evaluated using both shear wave velocity (Vs) shown by pSWE and the liver fibrosis index (LFI) shown by RTE, while a liver biopsy sample was obtained from the same area that was subjected to an elastography examination. Results of the latter were compared with those obtained in a histological examination. Results: Multivariate analysis showed that Vs and LFI were significantly correlated with the liver fibrosis stage in all of the enrolled patients. Sub-analysis findings compared patients with and without non-alcoholic fatty liver disease (NAFLD) and demonstrated that Vs was significantly correlated with the liver fibrosis stage in both groups, whereas LFI was correlated with that only in the non-NAFLD patients. However, a multivariate analysis demonstrated a significant correlation between steatosis grade and LFI in the NAFLD patients. Conclusions: RTE is less useful than pSWE for assessing liver fibrosis in patients with NAFLD.